Effect of Phytase on the Sodium Requirement of Starting Broilers 2. Sodium Chloride as Sodium Source - Goodgame, S.D.; Mussini, F.J.; Lu, C.; Bradley, C.D.; Comert, N.; Waldroup , P.W. (International Journal of Poultry Science, 2011)
Recent studies have suggested that phytase enzymes may influence sodium (Na) metabolism in the chick. However, no studies have demonstrated that the dietary Na requirement itself is influenced by phytase supplementation. In the present study male broilers were fed diets with Na levels ranging from 0.10 to 0.28% using NaCl as the source of supplemental sodium. Diets were fed either without phytase or with 500 (1X), 1000 (2X), or 2000 (4X) FTU/kg of phytase. For 1X phytase the Ca and Nonphytate P (NPP) were reduced 0.10% each and 0.20% each for the 2X and 3X levels of phytase supplementation. The diets with 0.10% and 0.28% Na were blended to provide Na levels of 0.10, 0.13, 0.16, 0.19, 0.22, 0.25 and 0.28% Na. Aliquots of these diets were then supplemented with the 0, 1X, 2X and 4X levels of phytase in a 4 x 7 factorial arrangement of treatments, each of which was fed to six replicate pens of five male broilers in electrically heated battery brooders. Experimental diets and tap water were provided for ad libitum consumption from day of hatch to 18 d of age. At 16 d excreta samples from each pen were freeze dried to determine moisture, Ca and P content. At 18 d body weight and feed consumption were determined. Two birds per pen were killed by CO2 inhalation and tibias removed and subjected to bone breaking determination. Chicks fed diets with the different levels of phytase with diets adjusted for anticipated release of Ca and P did not differ significantly in BW, Feed Conversion (FCR), mortality, or fecal moisture content, indicating that the adjustments made for anticipated release of Ca and P was adequate in relation to these measurements. Sodium levels of the diet had significant effects on BW, FCR and fecal moisture. Fecal moisture increased with each level of sodium, so lower dietary levels would be beneficial in this regard. No significant effects on mortality were noted for sodium levels. No significant interactions were noted between sodium level and phytase supplementation for BW, FCR, fecal moisture, or mortality. Regression analyses suggested a sodium requirement of 0.21±0.02% for BW and 0.15±0.01% for FCR. Estimates of sodium requirement at different levels of phytase supplementation did not show any consistent effect of phytase supplementation on the sodium requirement for BW or FCR. Therefore there is no evidence that phytase supplementation will modifiy the dietary sodium requirement of the broiler chick.